Tingkat Kerentanan Sosial Ekonomi Masyarakat Nagari Simabur Kecamatan Pariangan kabupaten Tanah Datar - Engga Prima Latifa; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2019)
This study purpose to assess the social and economic vulnerability of the community to volcanic disasters in each jorong in Nagari Simabur, Pariangan District, Tanah Datar District. This type of research is descriptive quantitative with the population being all households in Nagari Simabur. Sample size determination uses the Slovin formula so that a sample of 88 respondents was obtained. The sampling technique used was simple random sampling. Data collection techniques using questionnaires, field observasions and documentation with data analysis techniques, namely scoring analysis. Scoring analysis is done by giving scores on each variable used in the study. Social vulnerability in this study was measured by geographical population density, agrarian population density, education, number of family members, dependency ratio and sex ratio. Economic vulnerability is measured by employment, income and area of agricultural land. The results of the socio-economic vulnerability analysis show that in Jorong Simabur and Jorong Tanjung Limau have a very vulnerable level of vulnerability which is more influenced by economic aspects, while in Jorong Koto Tuo has a rather vulnerable level of vulnerability which is more influeced by social aspects.